The Evolution of Property Rights in Indonesia (Journal of Indonesian Legal Studies, 2024)
The article explains the emergence of property rights over land in Indonesia. Theoretically, the emergence of property rights in Java was deliberate. It is contrasts with the claim that spontaneous evolution of property rights . The article contributes to explaining the deliberate emergence of property rights in the case of the emergence of property rights to land in Java, Indonesia. The study is conducted by tracing the handover traces of land policy development from each period of power. The policy study begins in the period of feudalism where the concept of vorstendomain prevailed. During this period, awareness of property rights had not yet grown because the population considered the land to be the property of the king. Javanese colonialism and its land policy started the seedbed for the emergence of property rights over land. The Priangan system during the VOC started the realisation for the Javanese population about land ownership. Raffles' land-tax further solidified the awareness of land ownership rights. At this time, land distribution occurred to the local elite. The cultuure stelsel policy during Dutch colonialism had weakened land claims for Javanese people, because the workload that had to be borne was in accordance with the amount of cultivated land. Liberalism that grew in Europe had influenced changes in land policy in Java. In 1870, the Dutch colonial government issued the agrarisch wet which recognised land ownership rights for indigenous people in Java.